Methods and TechniquesKnuckle technique guided by intravascular ultrasound for in-stent restenosis occlusion treatment - Tasic, Mladen; Sreckovic, Miodrag J.; Jagic, Nikola; Miloradovic, Vladimir; Nikolic, Dusan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
One of the rarest lesions is in-stent restenosis chronic total occlusion (CTO). Limited data suggest that the treatment success rate is dependent on the possibility to cross into the lumen of an occluded stent, and the decision about what technique to use varies by operator preference. The knuckle technique is used to create a deliberate dissection plane in various CTO techniques. A guide wire is pushed until a complex loop is formed and advanced through the lesion. In this report we present a case where a knuckle wire guided by intravascular ultrasound control is used to penetrate the distal cap in an in-stent restenosis CTO lesion.